Rigorismus oder pastorales Entgegenkommen?: zur Entstehung des kirchlichen Bußverfahrens im 2. Jahrhundert - Dünzl, Franz (Zeitschrift für katholische Theologie, 2005)
The importance of Herm for the penitential practice of the church is still much discussed as to whether he is a rigorist in limiting repeated penance or whether he is lenient in allowing a last chance for penance. The author argues for this discussion as a wrongly posed alternative since Herm argues for a last chance, but for the first time includes severe sins such as denying the faith and adultery. Legitimized by visions, the book found widespread reception and worked as a catalyst for later attempts to solve the problem.